Konsep Pendidikan Sosiologi Menurut Perspektif Ibn Khaldun - Fery Yanto (Rayah Al-Islam, 2020)
This article describes the concept of sociological education according to Ibn Khaldun's perspective. The fact of sociology education is to maintain and strengthen people's social relationships in order to stay harmony and peaceful while paying attention to the values of Islamic teachings in accordance with the Qur'an and Sunnah. As a study of the intellectual history of sociological thinking, the research method used in this discussion is through historical and sociological approaches obtained through the study or study of libraries (library research) that is qualitative descriptive, namely trying to uncover, analyze, present data and facts related to this discussion through primary data taken directly in the Book of Muqaddimah and secondary data taken from other relevant books in this discussion. As for the results of this study is finding the extraordinary fact that it turns out that Ibn Khaldun's thoughts on social sciences (sociology) and history are basically. Sociological theories and history became a foothold in modern intellectuals although the big names were dimmed during the golden age of European intellectuals The role of orientalists and Muslim scholars examining the thinking of 14th-century Muslim scholars opened the world's eyes to the quality of the thinking of Muslim scholars and should be studied as a scholarly speciality, especially in the field of social and historical sciences. Even modern thinkers have not been able to match his thinking.